2022
DOI: 10.3389/fnut.2022.872169
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Effects of Human Physiology, Psychology, and Individual Variations on Satiety–An Exploratory Study

Abstract: Satiety can influence food intake, and as a consequence has the potential to affect weight and obesity. Human factors such as physiology and psychology are likely to be important in determining satiety. However, it is not well-understood how these factors (individual variations) alone or combined contribute to satiety feelings. In addition, there have been limited or no attempts to use a holistic approach to evaluate satiety. In this study, three plant-based foods were used as mid-morning snack for 52 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Various experimental and clinical studies have unequivocally demonstrated that adipose tissue, liver, muscle, and pancreas exhibit inflammation in individuals with obesity and T2DM. Macrophages infiltrate these tissues in animal models of obesity and diabetes and with metabolic syndrome or T2DM [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental and clinical studies have unequivocally demonstrated that adipose tissue, liver, muscle, and pancreas exhibit inflammation in individuals with obesity and T2DM. Macrophages infiltrate these tissues in animal models of obesity and diabetes and with metabolic syndrome or T2DM [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental and clinical studies have unequivocally demonstrated that adipose tissue, liver, muscle, and pancreas exhibit inflammation in individuals with obesity and T2DM. Macrophages infiltrate these tissues in animal models of obesity and diabetes and with metabolic syndrome or T2DM [3,4]. Serum inflammatory markers, including interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP), are increased in obese individuals, suggesting that diabesity can be characterized as an inflammatory condition [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to take into account the impacts of both individual and food variances for holistic studies that concentrate on the study of human satiety responses to foods. Multiple domains (physiology, psychology, eating and type of food) must be taken into account in order to comprehend the factors that influence perceived satiety, and there are significant individual variations that are in part influenced by external and internal factors ( 14 ). Therefore, it is essential to analyze the physiological as well as behavioral aspects to completely understand the role of satiety and satiation in individual eating behavior.…”
Section: Introductionmentioning
confidence: 99%